Social media as a public space for political activism: the use of Twitter during Gezi Park protests / Begüm Burak - Burak, Begüm (Faculty of Communication & Media Studies, 2021)
Political polarization in Turkey has not only been visible during electoral processes but it has also been evident in non-electoral processes in online and offline protests. Gezi Park protests in 2013 denote to such processes. This study analyzes the use of Twitter during Gezi Park protests that had sparked a big polarization. The role of Twitter had been influential in mobilizing the masses in the protests. During Gezi protests as seen in the Arab Spring, Twitter was used by the protesters in a dense way in the polarized political environment. Using the “mediated populism” as the theoretical framework, this study argues that social media has paved the way for the emergence of a citizen-centered public space in times of crisis and polarization during Gezi protests. The data that will be under analysis consist of the tweets posted on Twitter during the peak of Gezi protests. The date between May 25 and June 16, 2013 is taken as the time span that refers to the peak time of protests. By detecting top-mentioned tweets, this study aims to analyze how political activism had been expressed by the protesters. To achieve this aim, the randomly selected tweets posted in this time span were examined by conducting content analysis methodology.